Pengaruh Jenis Katalis pada Elektroda Pembanding terhadap Efisiensi Dye Sensitized Solar Cells dengan Klorofil sebagai Dye Sensitizer: Nurrisma Puspitasari, Siti Rabiatul Adawiyah, Muhammad Noer Fajar, Gatut Yudoyono, Agus Rubiyanto, Endarko - Nurrisma Puspitasari, Nurrisma Puspitasari; Siti Rabiatul Adawiyah, Siti Rabiatul Adawiyah; Muhammad Noer Fajar, Muhammad Noer Fajar; Gatut Yudoyono, Gatut Yudoyono; Agus Rubiyanto, Agus Rubiyanto; Endarko, Endarko (Jurnal Fisika dan Aplikasinya, 2025)
Dye-sensitized Solar Cell (DSSC) is a dye sensitized solar cells are formed by a sandwich structure where there are five parts include: glass ITO (Indium Tin Oxide) as a substrate; TiO2 as a semiconductor material; chlorophyll dye as an electron donor; electrolyte as electron transfer. Nanometer-sized TiO2 powder obtained through synthesis by coprecipitation method. Measurements were taken at the power of 100 mW/cm2. The results of the efficiency of DSSC using active carbon as a catalyst in the reference electrode, produces a larger percentage than black carbon and graphite, which is of 0.05% for active carbon, black carbon to 0.032%, 0.029% for graphite.